Prey odour enhances swimming activity and feed intake in the Senegalese sole - Barata, E. N. (2014)
Olfaction is important in many aspects of the life-history of fishes including feeding, and more so in nocturnal benthic feeders. In the current study we assessed the importance of olfaction in food-search behaviour of the Senegalese sole, an economically important marine species both as farmed and wild-caught. Whole-body homogenates of the polychaete Diopatra neapolitana were fractionated by solid-phase extraction (SPE) using C18 cartridges and the olfactory potency of the resultant fractions (hydrophobic eluate and hydrophilic filtrate) was assessed by the electro-olfactogram in juvenile sole. In addition, the effect of both the homogenate and SPE fractions on sole locomotion was assessed in a flow-through tank (fluviarium). Finally, whole-body homogenate was added to commercial feed pellets and tested whether it could enhance food consumption by sole. The SPE hydrophilic filtrate contained the majority of the olfactory activity found in the whole-body homogenate. Both the homogenate and filtrate, but not the eluate, increased number of movements, time moving, linear velocity, distance travelled and time swimming upstream of sole in the fluviarium; ablation of the olfactory epithelia disrupted these behavioural responses to the homogenate. Intact sole consumed more pellets flavoured with worm homogenate than those without. These results show that olfaction plays an important role in food-search behaviour of the Senegalese sole and that the hydrophilic fraction of D. neapolitana whole-body homogenate contains key substances affecting sole search behaviour; moreover, ingestion by sole was enhanced by addition of worm homogenate to the dry feed pellets.